Coal dust nanoparticles in the ambience of mine workings and their environmental hazard - Onischuk, A.A.; Paleyev, D.Yu.; Baklanov, A.M.; Dubtsov, S.N.; Zamaschikov, V.V.; Korzhavin, A.A. (Publishing House of the KarSU named after E.A.Buketov, 2016)
The authors studied the mechanism of formation of nanoscaled aerosol at mechanical destruction of coal both by a shearer and in a continuous flow mill under laboratory conditions. They found that the spectrum and morphology of particles formed in a laboratory mill are in line with those of the nanoaerosol formed in a mine. The investigation of ignition of a methane-air-nanoaerosol mixture in a spherical reaction vessel with 10 liters volume showed that such a mixture becomes essentially more explosive. This made itself felt both by the growth of the maximum explosion pressure, and a significant increase in its rate of rise. The studies suggested that the nanoaerosol was originated from organic compounds contained in the coal transforming into the gaseous phase at the local heating of the coal on shearer bits.
Keywords: nanoaerosol; coal dust; nucleation; methane-air mixture; ignition; explosion; flame front